2015
DOI: 10.1039/c5ra06016h
|View full text |Cite
|
Sign up to set email alerts
|

A biosensor based on a film bulk acoustic resonator and biotin–avidin system for the detection of the epithelial tumor marker mucin 1

Abstract: AlN thin film bulk acoustic resonators (FBARs) with a resonant frequency of $575 MHz have been fabricated to function as an epithelial tumor marker mucin 1 (MUC1) biosensor. Streptavidin was assembled on the sensitive area of FBAR. After the recognition between aptamers-AuNP conjugates and MUC1, biotin, along with the conjugates, was captured by streptavidin onto the surface of FBARs. Therefore, the target MUC1 could be sensitively detected. This biosensor exhibited a good linear relationship between the frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The aptamers have been presented as new analytical tools for tumor markers as an alternative for antibodies, because of their ability to withstand repeated rounds of denaturation/renaturation, and retain their structures, moreover, they are temperature resistant and do not require refrigeration and can be selected against toxic compounds and non‐immunogenic compounds, target small molecules, also they can be easily modified for attachment and signaling . Recently, few studies have reported the detection of MUC1 aptamer‐based biosensors . Cheng et al.…”
Section: Introductionmentioning
confidence: 99%
“…The aptamers have been presented as new analytical tools for tumor markers as an alternative for antibodies, because of their ability to withstand repeated rounds of denaturation/renaturation, and retain their structures, moreover, they are temperature resistant and do not require refrigeration and can be selected against toxic compounds and non‐immunogenic compounds, target small molecules, also they can be easily modified for attachment and signaling . Recently, few studies have reported the detection of MUC1 aptamer‐based biosensors . Cheng et al.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In recent decades, owing to excellent piezoelectric property, better quality factor, and high electromechanical coupling coefficient, ZnO is becoming a very promising candidate for FBAR devices as a piezoelectric material. [13][14][15][16] However, ZnO have the drawback of low longitudinal acoustic wave velocity and low resistance, which limits its application to high sensitivity acoustic sensors. 17 Mg X Zn 1ÀX O, a ternary compound formed by alloying ZnO and MgO, has attracted more and more attention due to its special properties such as higher acoustic velocity and resistance than that of ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…Biosensors are analytical devices which combine a biologically sensitive element with a physical transducer to selectively and quantitatively detect the trace of biomarkers such as DNA (Auer et al 2011;Lin et al 2010;Nirschl et al 2009), proteins (Kanno et al 2000;Nirschl et al 2009;Quan et al 2011;Quershi et al 2009;Sapsford and Ligler 2004;Zhao et al 2012a), and cells (Ayala et al 2009). There are different technologies that have been used for biosensors, such as electrochemical impedance spectrometry (EIS) (Ge et al 2014;Zhu et al 2014), surface plasmon resonance (SPR) (Cao et al 2006;Liedberg et al 1983), micro-cantilever (MCL) Lee et al 2007) and acoustic wave (Flewitt et al 2015;Guo et al 2015;Katardjiev and Yantchev 2012;Nirschl et al 2010;Voiculescu and Nordin 2012). The electrochemical biosensors typically have low sensitivity, while the other two types of technology-based biosensors have very high sensitivity, but are very expensive to manufacture and complex in operation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the acoustic wave-based devices are less expensive without compromising their sensitivity. Bulk acoustic wave (BAW) resonators have been widely employed as sensors for detecting variables such as mass García-Gancedo et al 2013;He et al 2011;Mai et al 2004;Nagaraju et al 2014;Rey-Mermet et al 2006), ultra-violet light (Bian et al 2015), infrared light (Wang et al 2011a), ozone (Wang et al 2011b), pressure (Giangu et al 2015), humidity (Zhang et al 2015a), volatile organic compounds (Chang et al 2016;Lu et al 2015), air pollution and biomarkers (Chen et al 2015b;Dickherber et al 2008;Guo et al 2015;Tukkiniemi et al 2009;Weber et al 2006;Wingqvist et al 2008) owing to their high sensitivity, real-time detection, label-free and wireless capabilities (Voiculescu and Nordin 2012). Table 1 compares the mostly reported technologies used in biosensors.…”
Section: Introductionmentioning
confidence: 99%